Cladonia rangiferina F. H. Wigg. ... - Jarvis, Charlie (Linnaean Society of London in association with the Natural History Museum, 2007)
Lichen rangiferinus Linnaeus, Species Plantarum 2: 1153. 1753. "Habitat in Alpibus, Europae frigidae sylvis sterilissimis, Alpestris differt a sylvatico, ut flos plenus a simplici." RCN: 8238. Lectotype (Nourish & Oliver in Biol. J. Linn. Soc. 6: 259. 1974): Herb. Linn. No. 1273. 240 (LINN). Current name: Cladonia rangiferina (L.) Weber ex F.H. Wigg. (Cladoniaceae). Note: See review by Jørgensen & al. (in Bot. J. Linn. Soc. 115: 347-349, 380, f. 53. 1994). ... : Published as part of Jarvis, Charlie, 2007, Chapter 7: Linnaean Plant Names and their Types (part L), pp. 610-650 in Order out of Chaos. Linnaean Plant Types and their Types, London :Linnaean Society of London in association with the Natural History Museum on page 629, DOI: 10.5281/zenodo.291971 ...